2011
DOI: 10.1161/circulationaha.111.036061
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemotactic Protein-1 Promotes Inflammatory Vascular Repair of Murine Carotid Aneurysms via a Macrophage Inflammatory Protein-1α and Macrophage Inflammatory Protein-2–Dependent Pathway

Abstract: Background Up to 5% of the population may have a brain aneurysm, and if the brain aneurysm ruptures, there is greater than 50% mortality, and more than onethird of survivors are dependent. Brain aneurysms detected before rupture can be treated to prevent rupture, or ruptured aneurysms can be treated to prevent re-rupture. Endovascular coiling of brain aneurysms is the treatment of choice for some aneurysms; however, up to one quarter of aneurysms may recur. The coiled aneurysms that do not recur are characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 58 publications
3
63
0
1
Order By: Relevance
“…30 MCP-1 is one of the key chemokines of the C-C chemokine family that regulate the migration and infiltration of macrophages. 31 In the present study, we have shown that the MCP-1-induced EMT of MCF-7 breast carcinoma cells is tightly correlated with accelerated wound healing and enhanced cell migration and invasion. We demonstrated that MCP-1-stimulated tumorigenic signaling with repressed expression of E-cadherin and upregulated expression of vimentin and fibronectin.…”
Section: Discussionmentioning
confidence: 49%
“…30 MCP-1 is one of the key chemokines of the C-C chemokine family that regulate the migration and infiltration of macrophages. 31 In the present study, we have shown that the MCP-1-induced EMT of MCF-7 breast carcinoma cells is tightly correlated with accelerated wound healing and enhanced cell migration and invasion. We demonstrated that MCP-1-stimulated tumorigenic signaling with repressed expression of E-cadherin and upregulated expression of vimentin and fibronectin.…”
Section: Discussionmentioning
confidence: 49%
“…Thus, local IP-10 may attract fibroblasts from the adventitia or perhaps circulating fibrocytes into the thromboembolic material leading to a persistent accumulation of those cells that secrete collagen and may cause growth and stiffening of this endovascular material. Also MCP-1, MlP1a and IL-6 were shown to promote migration of monocytes, macrophages and fibroblasts [26,27]. Furthermore, MCP-1-induced inflammation can lead to neointimal hyperplasia [28,29] and also stimulates fibroblast proliferation and collagen secretion [30].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, MCP1 is important for the attraction of monocytes, which clearly aggravates aneurysm pathology, but it also plays a role in tissue repair, which alleviates aneurysm development. 9,37,38 Interestingly, the role of CCL5 is more apparent because recently, Iida et al 39 showed in 2 different AAA mouse models that inhibition of CCL5 prevented AAA development and progression. In addition, a polymorphism has been described for the receptor of CCL5 (CCR5 Δ32 deletion) that correlates with aneurysm formation in 2 of 3 human studies, [40][41][42] which suggests an active role for CCL5 in the human aneurysm.…”
Section: Discussionmentioning
confidence: 99%